2012
DOI: 10.1080/17539153.2012.684970
|View full text |Cite
|
Sign up to set email alerts
|

British Muslims and the discourses of dysfunction: community cohesion and counterterrorism in the West Midlands

Abstract: This article analyses how British discursive representations of Muslims during the last decade were utilised in a local context during the planning stages of a proposed mosque in the West Midlands town of Dudley. Locating the central narratives in dominant national discourses of community cohesion and counterterrorism, this article analyses how correspondents to a local newspaper re-articulated national representations of Muslims as culturally dysfunctional in a local context and used these representations to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…In another study, it was argued that the representation of Muslims and Irish communities in the British press constructed them ‘suspect’ ( Nickels et al., 2012 ). Moreover, Kassimeris and Jackson (2012) critically analyzed correspondents' letters about building ‘Dudley Mosque’ published in UK newspapers, which revealed that Muslims were perceived as threat to the national and local culture of UK. Thus, they were inherently regarded as ‘others’.…”
Section: Resultsmentioning
confidence: 99%
“…In another study, it was argued that the representation of Muslims and Irish communities in the British press constructed them ‘suspect’ ( Nickels et al., 2012 ). Moreover, Kassimeris and Jackson (2012) critically analyzed correspondents' letters about building ‘Dudley Mosque’ published in UK newspapers, which revealed that Muslims were perceived as threat to the national and local culture of UK. Thus, they were inherently regarded as ‘others’.…”
Section: Resultsmentioning
confidence: 99%
“…Nickels et al (2012, 352) found that by articulating a distinction between moderate Muslims and radical Islamists the national and regional press contributed to the construction of Muslim communities as "a two-faced Janus, with the law abiding always defined in relation to extremists". This narrative served to frame British Muslims as the constitutive other and the source of the threat posed by contemporary terrorism, placing the burden of challenging violent extremism squarely upon the shoulder of Muslim communities (Allen 2004(Allen , 2007Kassimeris and Jackson 2012;McGhee 2008).…”
Section: Critical Studies On Terrorismmentioning
confidence: 99%
“…Reinforcing the notion that mosques perform symbolic functions, Jonker's (2005) findings illustrated the extent to which geo-political factors and incidents became as determinative as did any local or national equivalent. Developed by Allievi (2009), Göle (2011), Kassimeris andJackson (2012), Tamimi Arab (2013) and Kuppinger (2014) among others, new mosques became proxies for all that was perceived to be problematic about Muslims and Islam.…”
Section: The Contemporary Problematisation Of Mosques In 'The West'mentioning
confidence: 99%
“…Similar findings were evident in the various studies investigating opposition towards the proposed new mosque in Dudley, England. While Reeves, Abbas and Pedroso (2009) and Kassimeris and Jackson (2012) offered competing perspectives, Allen's (2013Allen's ( , 2014Allen's ( , 2015aAllen's ( , 2015b studies afforded particular insight into the breadth of opposition including allegations that included the mosque having a detrimental impact on the town's medieval skyline, its minaret being problematically taller than a nearby church steeple, as evidence of the 'Islamification' of Britain, as a hub of radicalisation and a destination for Islamist terror groups. An amalgam of the local, national and international, Allen's studies evidenced the extent to which the perceived, albeit deemed 'real', threat posed by the 'Otherness' of Muslims and Islam informs these discourses.…”
Section: The Contemporary Problematisation Of Mosques In 'The West'mentioning
confidence: 99%